Classification-Card Media: Its Effect towards Learning Achievement in Biology Subject - Angela, Lia; Noveri, Mitra; Tiara, Tiara (Indonesian Journal of Science and Mathematics Education, 2020)
This research aims to determine the effect of the application of classification card media to the learning achievement. This research is a quasi-experimental study. The population of this research is the students of class X Science of SMA Negeri 7 Kerinci. The sample class is students of Class X Science 1 as an experimental class and Class X Science 2 as a control class. The research instrument is a test with objective questions. The final test result data were analyzed using t-test. The results of the t-test analysis showed that the application of the classification card media could improve student learning achievement.